Prosedur Pengembangan Instrumen Tes Evaluasi Hasil Belajar Siswa di SD Muhammadiyah 1 Gondrong Kota Tangerang - Ina Magdalena; Syifa Fauziah; Febri Awalia; Nurul Maulida (RC-INSTITUT, 2020)
This study was made to find out how the development of instruments in primary schools, how to apply them, how to make instruments and find out assessing the level of difficulty on the instruments made. This research was conducted at SD Muhammadiyah 1 Gondrong Kec. Cipondoh Kot. Tangerang, by interviewing three educators at the school to get the desired information. The research method used by the author in this study is a qualitative method. Qualitative research can start from a theory that has been acknowledged for its truth and can be compiled at the time the research takes place based on data collected.